Assessment of energy efficiency and environmental performance of led light sources by the ecodesign methods - Nazarenko, Vasyl; Sorokin, Viktor; Pekur, Demyd; Shpak, Svitlana; Basova, Iuliia; Baghirov, Sabir; Kozhushko, Gregory (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the study is the processes and factors that determine the energy efficiency and environmental friendliness of LED light sources and contribute to reducing negative impacts on the environment and human health. The work investigated the levels of energy efficiency and environmental friendliness of commercial samples of LED luminaires for compliance with the requirements of the EU Commission Regulations on Energy Labeling No. 2019/2015 and on Ecodesign No. 2019/2020. The network efficiency coefficient hTM (lm/W) was taken as the energy efficiency criterion. The main environmental friendliness criteria: the limit level of flicker luminance PstLM and the visibility of the stroboscopic effect SVM are established by the EU Commission Regulation No. 2019/2020; the limit level of blue light hazard should not exceed the risk group RG1 according to EN 62471:2018; the limit levels of the Unified Glare Rating UGR according to ISO 8995-1:2025. LED luminaires using high-power LEDs have a hTM coefficient of 135–170 lm/W and comply with energy efficiency classes D and C according to Commission Regulation EU No. 2019/2015. The hTM coefficient of luminaires with low-power LEDs is 100 lm/W, energy efficiency class F. Luminaires with low-power LEDs correspond to the RG0 risk group in terms of blue light safety, and luminaires with high-power LEDs correspond to the RG1 risk group. All tested luminaires meet the requirements of Commission Regulation EU No. 2019/2020 in terms of flicker luminance and visibility of the stroboscopic effect (PstLM < 1, SVM < 0.4). Light exceeding the established limit values for these indicators has a negative impact on health and can be classified as light pollution. Light sources have the greatest impact on the environment as a result of the consumption of electrical energy